Consumer Satisfaction and Online Purchase Decisions: Examining The Price and Product Analysis - Rezki Fani; Sri Wahyuni Nur; Adnan Hasan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This research is a quantitative descriptive study with a path analysis method that aims to determine the influence of price and product assessments on online purchasing decisions and their impact on consumer satisfaction. The population in the study were college students living in Maros County and were consumers of online shopping platforms. The total sample of 98 people was obtained by sampling method using purposive sampling technique. Based on the results of hypothesis testing using the smartPLS application version 3.0, it shows that of the seven hypotheses proposed, only the price variable has no direct effect on consumer satisfaction. While other hypotheses have a positive and significant influence both directly and through intervention variables